From Zomia to Holon: Rivers and Transregional Flows in Mainland Southeastern Asia, 1840-1950 - Iqbal, Iftekhar (수완나부미, 2020)
How might historians secure for the river a larger berth in the recent macro-historical turn? This question cannot find a greater niche than in the emerging critique of the existing spatial configuration of regionalism in mainland Southeastern Asia. The Brahmaputra, Irrawaddy, Salween, Mekong and Yangtze rivers spread out like a necklace around Yunnan and cut across parts of the territories that are known as South, Southeast and East Asia. Each of these rivers has a different topography and fluvial itinerary, giving rise to different political, economic and cultural trajectories. Yet these rivers together form a connected “water-world”. These rivers engendered conversations between multi-agentive mobility and large-scale place-making and were at the heart of inter-Asian engagements and integration until the formal end of the European empires. Being both a subject and a sponsor of transregional crossings, the paper argues, these rivers point to the need for a new historical approach that registers the connections between parts of the Southeast Asian massif through to the expansive plain land and the vast coastal rim of the Bay of Bengal and the China Seas. A connection that could be framed through the concept of Holon.